RECOVERY OF HAND ARTHRITIS BY PHYSICAL THERAPY - Codrin Prorociuc; Laura Ailioaie; Anca Iacob (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Rheumatoid arthritis has a chronic progressive evolution, requiring early and lasting intensive treatment. The disease predominates in women, being more frequent onset between 30-40ani. For this study, we had the three subjects diagnosed with rheumatoid arthritis with various forms of evolution. Each patient received an individualized physical therapy program. After the treatment was found an improvement of symptoms of rheumatoid arthritis: as the treatment was applied at an earlier stage of disease, the results were better.